Analisis Implementasi Dan Jenis-Jenis Akad Tabarru' Dalam Transaksi Keuangan Syariah: Analisis Implementasi Dan Jenis-Jenis Akad Tabarru' Dalam Transaksi Keuangan Syariah - Ilham Wahyudi; Wardatun Nafisah (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
The tabarru' contract is an important instrument in the Islamic economic system, which is based on the principles of mutual assistance and brotherhood. Unlike the tijari contract, which is oriented toward commercial profit, the tabarru' contract aims solely to seek the pleasure of Allah SWT and to help others. This article aims to describe the definition, classification, and urgency of various types of tabarru' contracts through a descriptive qualitative approach. The study results show that tabarru' contracts are divided into several main categories, such as loans, services, and grants, all of which function as social buffers in the Islamic financial system. A deep understanding of these contracts is essential for Islamic banking practitioners to create a humanistic economic ecosystem.